Seasonal variation in vitamin D status in professional soccer players of the English Premier League - Morton, J. P.; Iqbal, Z.; Drust, B.; Burgess, D.; Close, G. L.; Brukner, P. D. (Applied Physiology, Nutrition, and Metabolism, 2012)
The prevalence of seasonal variation in vitamin D status was examined in 20 FA Premier League soccer players residing at a latitude of 53°N. Serum 25-hydroxyvitamin D (25(OH)D) levels decreased (P < 0.001) between August (104.4 ± 21.1 nmol/L, range 68-151) and December (51.0 ± 19.0 nmol/L, range 22-86), such that levels for 65% of the sample were insufficient (<50 nmol/L) in winter. Strategies to augment vitamin D3 availability may therefore be advantageous for UK soccer players so as to maintain muscle function.